The Evolution of the 2003 Convention and the Challenges Facing the Protection of Intangible Cultural Heritage in the Arab World - Ouiza GALLEZE (Turath, 2024)
The 32nd session of the General Conference of UNESCO adopted the Convention for the Safeguarding of Intangible Cultural Heritage on October 17, 2003. Twenty years after, comes the opportunity for UNESCO, Member States and all stakeholders involved in safeguarding living heritage to show that heritage belongs to everyone.